ACCURACY ASSESSMENT OF OBJECT ORIENTED IMAGE SEGMENTATION - Narieswari, Lalitya (GEOMATIKA, 2009)
Visual review and comparison based on reference areas (correspondence and shape conformity) were employed in this study to assess the segmentation quality. The segmentation procedure was applied to segment aerial photographs in nature areas in part of The National Park Veluwezoom near Rheden, The Netherlands. The segmentations were generated using the top down approach, which is implemented in the Definiens Developer software. Comparison of the segmented images with the references gave a fair result by giving 45.8 % of exact correspondence and good conformity for all object properties which tested. Keywords: image segmentation, object-oriented analysis, accuracy assessment. ABSTRAK Visual review dan perbandingan berdasar pada area referensi (correspondence and shape conformity) digunakan pada syudi ini untuk mengukur kualitas hasil segmentasi. Segmentasi dilakukan pada foto udara untuk mengekstrak nature area di sebagian taman nasional Veluwezoom, Rheden, Belanda. Segmentasi dilakukan dengan pendekatan top down menggunakan perangkat lunak Definiens Developer. Perbandingan antara hasil segmentasi dengan referen memberikan hasil yg cukup baik dengan correspondence sebesar 45.8% dan conformity yang baik untuk semua object properties yang diuji.